`Setting the benchmark` Part 2: contextualising the physical demands of teams in the FIFA World Cup Qatar 2022 - Btradley, P. S. (Biology of Sport, 2024)
This study aimed to contextualise and benchmark the physical demands of teams in the FIFA World Cup Qatar 2022. With FIFA`s official approval, all sixty-four games were analysed during the competition (n = 32 teams) using a multi-camera computerised tracking system. On average, teams during Qatar 2022 covered around 108.1 ± 3.6 km in total, with 9.0 ± 0.9 and 2.3 ± 0.3 km covered at the higher intensities (=20.0 and =25.0 km · h-1), respectively. Compared to the FIFA World Cup Russia 2018, national teams in Qatar 2022 covered only 3% more total distance but 16-19% more distance at the higher intensities (P < 0.01; Effect Size [ES]: 0.9-2.0). When the data was adjusted based on the number of minutes played, tournament differences at the higher intensities were less pronounced (9-12%; P < 0.01; ES: 0.7-1.3). The United States, Canada, Saudi Arabia, Germany and IR Iran covered 19-34% more high-intensity distance than Argentina, Ecuador, Qatar, Poland and Costa Rica during the 2022 tournament (P < 0.01; ES: 3.2-3.5). Match-to-match variation of each team in Qatar 2022 revealed Ecuador and Uruguay were particularly consistent for the distances covered at higher intensities (Coefficient of Variation [CV]: 2-3%), whilst Japan demonstrated considerable variation (CV: 23-29%). Teams generally covered more total distance on a per-minute basis in the first versus the second half (P < 0.01; ES: 1.2), but no differences existed at higher intensities (P > 0.05; ES: 0.0-0.1). Correlations between the number of high-intensity runs and various phase of play events across all teams were strongest for defensive transitions and recoveries, in addition to progressions up the pitch and into the final third (r = 0.63-0.75; P < 0.01). The present findings provide valuable context into the contemporary team demands of international football. This information could be useful for practitioners to benchmark team performances and to potentially understand the myriad of factors impacting physical performances.